Investigating students’ MALL experience in light of an ecological perspective - Adriadi Novawan; Siti Aisyiyah; Fitri Wijayanti; Alfi Hidayatu Miqawati; Nodistya Septian Indrastana (Journal of English in Academic and Professional Communication, 2019)
The paper reports a study inspired by the notion of ecological linguistics which has much been reviewed and researched by the applied linguistics experts worldwide. In this study, Leo van Lier’s notion of action-based was mainly used to describe the reality of English learning experience of university students enrolling in non-English departments. The English Courses in the departments applied MALL which was designed based on the ecological teaching principles of action-based (AB). Open-ended interviews were done to four participants to explore their perspectives on their own experience of learning English before and after joining the English courses. The data were analyzed and interpreted through narratives to unveil the elements of past, present, and future of the learning experience. Participant confirmation was carried out to increase the validity of the research findings. There was obvious evidence that the application of MALL underpinned by action-based teaching nurtured the students’ecological learning habit which connects the English and content-subject learning. All participants perceived that such learning was firstly complicated but challenging and motivating.